The Relationship Between the Distribution of Training Intensity and Performance of Kayak and Canoe Sprinters: A Retrospective Observational Analysis of One Season of Competition - Matzka, Manuel; Leppich, Robert; Holmberg, Hans-Christer; Sperlich, Billy; Zinner, Christoph (Frontiers in Sports and Active Living, 2022)
To evaluate retrospectively the training intensity distribution (TID) among highly trained canoe sprinters during a single season and to relate TID to changes in performance. The heart rates during on-water training by 11 German sprint kayakers (7 women, 4 men) and one male canoeist were monitored during preparation periods (PP) 1 and 2, as well as during the period of competition (CP) (total monitoring period: 37 wks). The zones of training intensity (Z) were defined as Z1 (<80% of peak oxygen consumption [VO2peak]), Z2 (81%-87% VO2peak) and Z3 (>87% VO2peak), as determined by 4 x 1500-m incremental testing on-water. Prior to and after each period, the time required to complete the last 1500-m stage (all-out) of the incremental test (1500-m time-trial), velocities associated with 2 and 4 mmol·L-1 blood lactate (v2[BLa], v4[BLa]) and VO2peak were determined. During each period, the mean TID for the entire group was pyramidal and total training time on-water increased from 5.0 ± 0.9 h (PP1) to 6.1 ± 0.9 h (PP2) and 6.5 ± 1.0 h (CP). The individual ranges for Z1, Z2 and Z3 were 61-96%, 2-26% and 0-19%. During PP2 VO2peak (25.5 ± 11.4%) markedly increased markedly compared to PP1 and CP and during PP1 v2[bla] [3.6 ± 3.4%] showed greater improvement compared to PP2, but not to CP. All variables related to performance improved as the season progressed, but no other effects were observed. With respect to time-trial performance, the time spent in Z1 (r = 0.66, p = 0.01) and total time in all three zones (r = 0.66, p = 0.01) showed positive correlations, while the time spent in Z2 (r = -0.57, p = 0.04) was negatively correlated. TID was pyramidal during the entire period of observation, with a tendency towards improvement in VO2peak, v2[bla], v4[bla] and time-trial performance. During PP2, when the COVID-19 lockdown was in place, the proportion of time spent in Z3 doubled, while the time in Z1 was lowered; total training time on-water increased; and to allow this increase, the CP proportions of Z2 and Z3 were decreased in favor of Z1.